A taxonomic revision of the genus Asiobaccha Violovitsh (Diptera: Syrphidae). Issue 41 (9th November 2016) - Mengual, Ximo
ABSTRACT: The flower fly genus Asiobaccha Violovitsh is revised and 10 new species are described: A. aea Mengual & Thompson, A. albipeza Mengual, A. aquila Thompson & Mengual, A. doesburgi Mengual, A. marissae Mengual, A. maculosa Mengual & Thompson, A. notofasciata Thompson & Mengual, A. samoaensis Mengual, A. selsi Mengual and A. taronja Mengual. Moreover, lectotypes are designated for Baccha semifumosa Meijere, Baccha luteolimbata Meijere, Asiobaccha nubilipennis (Austen), A. praefica (Bezzi), A. virtuosa (Curran) and A. sauteri (Kertész), and a neotype for A. loriae (Meijere) is also designated. New synonyms are proposed: Baccha schistaceifrons Meijere and Baccha semifumosa Meijer are synonymised under Asiobaccha bicolor (Austen); Baccha luteolimbata Meijere is a junior synonym of Asiobaccha tinctiventris (Meijere); Baccha flavipes Doesburg is a junior synonym of Asiobaccha tripartita (Walker); Baccha gigas Curran is a junior synonym of Asiobaccha virtuosa Curran; and the syntypes of Baccha sulica Austen are synonymised under Asiobaccha bicolor (Austen) and Asiobaccha tripartita . Diagnoses, illustrations, synonymies and distributional data are given for all described species. Descriptions of new species as well as an identification key to all known species are also provided. http://zoobank.org/urn:lsid:zoobank.org:pub:6B627B0F-9440-47F1-90F4-9AF4C7308A99